Chlorine dioxide is a broad-spectrum disinfectant against Shiga toxin-producing Escherichia coli and Listeria monocytogenes in agricultural water - Van Blair, Jared; Lacombe, Alison; Harvey, Beatrice L.; Wu, Vivian C. H. (Frontiers in Microbiology, 2024)
Agricultural water is commonly treated with chlorine-based disinfectants, which are impacted by water quality. Understanding how water quality influences disinfectants such as chlorine dioxide (ClO2) against pathogenic bacteria is important for creating efficacious sanitation regimens. In this study, the minimum inhibitory concentration (MIC) of ClO2 needed to achieve a 3-Log reduction against Shiga toxin-producing Escherichia coli (STEC) and Listeria monocytogenes was compared across agricultural water samples. Sterile ddH2O served as a control to compare with environmental samples from Salinas Valley, CA, and laboratory standards. To test different dosages and water qualities, stock ClO2 was diluted in 24-well plates with target concentrations of 10, 5, 2.5, and 1.25 mg/L. Well plates were inoculated with pathogens and treated with sanitizer for 5 minutes. Following treatment, surviving pathogens were enumerated using viable cell counts. The results demonstrate that groundwater samples had the highest water quality of the environmental samples and required the lowest concentration of disinfectant to achieve 3-Log reduction against both bacteria, with MIC between 1.4-2.0 mg/L. Open-source samples had lower water quality and required a higher concentration of ClO2 for 3-Log reduction, with MIC between 2.8 -5.8 mg/L for both pathogens. There was no correlation between pH, turbidity, or conductivity/TDS and reduction for either STEC or L. monocytogenes, suggesting no individual water metric was driving reduction. A lower dosage was required to achieve 3-Log reduction against STEC, while L. monocytogenes required greater concentrations to achieve the same level of reduction. Overall, these results help guide growers in using ClO2 as a broad-spectrum disinfectant and demonstrate its efficacy in reaching 3-Log reduction across agricultural water samples.